Culture influences towards international negotiation / A'fifah Mohd Yusof and Zuhanis Ahmad Rosdi - Mohd Yusof, A'fifah; Ahmad Rosdi, Zuhanis (Faculty of Business and Management, 2014)
Purpose - The purpose of this study is to investigate and identify on how culture influences through the relationship between SME's perceptions, national cultures, business norms, and religious values towards the international negotiation. Background - Context of negotiations at the international level is faced with the differences between various cultures: a long-term attitude towards communication, the power placement, the uncertainties avoiding, emotional differences between the negotiating parties and others. Differences in cross-cultural dimensions can influence the process of negotiations between representatives of different cultures in the negotiations. There may happen in a variety of misunderstandings in negotiations and between the two parties of the same culture, while the process of preparing for the talks with different cultures require the article discusses cultural dimensions, their effect on negotiations. Paper includes suggestions for further research of international negotiations. Method - The data has been collected from the owner/marketing/sales manager of SME's who registered as MATRADE's member by distributing questionnaire via email and so on. To test the hypothesis, SPSS 20.0 has been adopted for basic analysis purposes. Result - Results shows that the most significant variables that have an impact towards international negotiation are the business norms.Conclusion - From this research, it shows that SME's perceptions, national culture, business norms and religious values have a significant correlation that is give impact towards negotiating internationally. This statement is supported by the fact that the correlation analysis shows SME's perceptions, national culture, business norms, and religious values with (p=.OOO) have significant association with the dependent variable that is international negotiation.